CHARACTERIZATION OF WEAKLY PRIME SUBMODULE - Puspa Nur Afifah; Irawati Irawati (Diponegoro University, 2021)
Let R is a commutative ring with identity and M is a unital R-module. El-bast and Smith (1988) have researched and introduced the multiplication module. Prime submodule has been studied by Ameri (2002). Then Atani and Farzalipour (2007) have extended the prime submodule to weakly prime submodule. Some properties were proved on each paper. This paper will study about characterization of weakly prime submodules.